Direct‐Current Triboelectric Nanogenerator Realized by Air Breakdown Induced Ionized Air Channel. Issue 27 (16th August 2018) - Luo, Jianjun; Xu, Liang; Tang, Wei; Jiang, Tao; Fan, Feng Ru; Pang, Yaokun; Chen, Libo; Zhang, Yan; Wang, Zhong Lin
Abstract: The air breakdown phenomenon is generally considered as a negative effect in previous research on triboelectric nanogenerators (TENGs), which is always accompanied by air ionization. Here, by utilizing the air breakdown induced ionized air channel, a direct‐current triboelectric nanogenerator (DC‐TENG) is designed for harvesting contact‐separation mechanical energy. During working process, the charges first transfer from bottom to top electrodes through an external circuit in contact state, then flow back via the ionized air channel created by air breakdown in the separation process. So a unidirectional flow of electrical charges can be observed in the external circuit. With repeating contact‐separation cycles, continuous pulsed DC output through the external circuit can be realized. This working mechanism was verified by real‐time electrode potential monitoring, photocurrent signal detection, and controllable discharging observation. The DC‐TENG can be used for directly and continuously charging an energy storage unit and/or driving electronic devices without using a bridge rectifier. Owing to its simplicity in structure, the mechanism is further applied to fabricate the first flexible DC‐TENG. This research provides a significant fundamental study for DC‐TENG technology and may expand its application in flexible electronics and flexible self‐charging power systems. Abstract : The air breakdown phenomenon is generally considered as a negative effect in previous research. Here, by utilizing the air breakdown induced ionized air channel, a novel direct‐current triboelectric nanogenerator (DC‐TENG) is designed for harvesting contact‐separation mechanical energy. The working mechanism of the DC‐TENG is proposed and verified by real‐time electrode potential monitoring, photocurrent signal detection, and controllable discharging observation.